2019
DOI: 10.1515/npprj-2019-0018
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the paper surface properties on the ink transfer parameters in offset printing

Abstract: Paper has a crucial impact on the qualitative properties of printed product as properties of the paper’s surface directly impact the ink transfer, consequently, basic optical properties of the print. Although same ISO paper type, papers possess variable surface properties leading to different influence on the ink transfer. The aim of this research was to analyse influence of the surface properties of the paper, including surface free energy, smoothness and gloss of some standard papers used in lithography on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Paper properties are one of the most important factors affecting the completeness of the image transfer and image appearance 18 . Ink and paper interaction is unmapped research area with development and introduction of new inks and paper types to the market 19 . Therefore, dispersion of pigments, binding of pigments to paper surface, porosity of the paper surface, ink absorption surface tension, contact angle and viscosity are important parameters that should be studied.…”
Section: Introductionmentioning
confidence: 99%
“…Paper properties are one of the most important factors affecting the completeness of the image transfer and image appearance 18 . Ink and paper interaction is unmapped research area with development and introduction of new inks and paper types to the market 19 . Therefore, dispersion of pigments, binding of pigments to paper surface, porosity of the paper surface, ink absorption surface tension, contact angle and viscosity are important parameters that should be studied.…”
Section: Introductionmentioning
confidence: 99%
“…When analysing Figures 9 and 10, one should be guided by the following: the higher the GLCM energy and the lower the entropy, the less expressed the mottling is 29 . Therefore, when observing the results of GLCM analysis of cyan‐printed samples (Figure 9A‐D), it can be concluded that the addition of nanoparticles to the polycaprolactone primer did increase the mottling, especially on the gloss paper.…”
Section: Resultsmentioning
confidence: 99%
“…All optical measurements were carried out by means of an X‐rite eXact spectrophotometer. The Δ E ab was used to detect the differences between printed samples with and without the primers for each sample 29 . Measurements were carried out 10 times at different parts of each sample, with the measurement conditions set to illuminant D50, standard observer of 2° and filter M1.…”
Section: Methodsmentioning
confidence: 99%
“…Paper [5] reports the results of studying the quality of the offset printing process on standard types of paper, which differ in the characteristics of the printed surface. The authors found a significant correlation between the surface characteristics of the printed material and the imprint quality, which could optimize the printing process.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The authors of [8] determined that for digital inkjet printing, it is critical to control the level of color distortion, which is crucial to ensure high-quality color reproduction on imprints. Thus, the cited studies [3][4][5][6][7][8] mainly reflect the features in the influence of the surface characteristics of corrugated cardboard under standard printing conditions, which are regulated by standards [2].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%